A Study on the Correlation of Big 5 Personality Traits in Asians With Facial Contour Surgery. Issue 2 (1st March 2023) - Shi, Jiadong; Ma, Liping; Xu, Haisong; Zhou, Yanchun
Abstract : Purpose: The purpose of this study is to explore the present situation and related factors of big 5 personality in Asian patients with facial contour surgery and to provide experience for clinical individualized medical care. Methods: Total 235 patients with facial contour surgery were selected in this study. The Neo Five-factor Inventory was used to investigate them. Results: The scores of conscientiousness and openness in the Neo Five-factor Inventory were higher than others, whereas neuroticism score was lowest in patients with facial contour surgery. The scores of extroversion and agreeableness were in the middle level. Among the big 5 personality the age, educational background, self-rated personality, the only child in a family and other cosmetic surgery history had significant differences in patients. Conclusions: Patients with facial contour surgery for different sex, different marital status, different body mass index, there is no significant difference in the big 5 personality through this study. However, older patients had higher score for conscientiousness, patients with higher educational background had higher scores in openness and patients with introverted personality had higher neuroticism score. The authors should take individualized personality traits during perioperative care to help the patients to establish a correct and healthy esthetic concept, as well as postoperative body image concept, to build their self-confidence and social competitiveness.